Employee Mobility and Organizational Outcomes - Mawdsley, John K.; Somaya, Deepak (Journal of Management, 2016)
A large and growing literature spanning multiple fields has identified employee mobility as a critical influence on several important organizational outcomes. However, extant research on the topic is highly fragmented and lacks a unifying theoretical framework, impeding the development of a cumulative conceptually integrated body of research. We seek to remedy this situation by undertaking a review of research on employee mobility and its organizational impacts and casting it within a novel integrative conceptual framework. As a critical foundation for this framework, we highlight how the various organizational impacts of employee mobility are ultimately engendered by different dimensions of human and/or relational capital that are conveyed by mobile individuals. Building on this foundation, we describe how multilevel contextual factors—characterized as attributes of the employee, source and destination firms, and environmental conditions—may moderate the transfer and utilization of human and relational capital held by mobile individuals. Finally, we review how constraining factors, such as labor market imperfections on both demand and supply sides, can impede employee mobility and also how alternative competing channels—for example, alliances, networks and geographic spillovers, and acquisitions—may be used for effectuating the same organizational impacts as mobility events. These constraints and competing channels are important because they circumscribe the conditions under which employee mobility can be a critical influence on organizational outcomes. We seek to provide a rich integrative theoretical understanding of employee mobility and spur future research on important unanswered research questions.